Comparative Study of the Grid Current Harmonic Attenuation in a Photovoltaic Generator Due to the Influence of the Synchronization Strategy - Guerrero-Rodríguez, N.F.; Ramírez-Rivera, F.A.; Batista-Jorge, R.O; Ferreira, Julio A.; Mercado-Ravelo, Robert (International Journal of Electrical and Computer Engineering Systems, 2025)
The present paper studies the current harmonic attenuation for four synchronization strategies commonly used in inverters for photovoltaic power generation. In a model of a 6kWp photovoltaic generator, the four synchronization strategies are implemented in the inverter controller. Real-time simulations are performed, for this purpose, the models of the photovoltaic generator and the utility grid were embedded in an OPAL-RT OP5707XG simulator. The distortion of the grid current for each synchronization strategy is analyzed using its corresponding frequency spectrum and a comparison is made with the IEEE Std. 519-2022 standard. The purpose of this test is to observe the effect of the synchronization strategy on the harmonic attenuation of the grid currents. The results show that one of the synchronization strategies evaluated in this work may be sufficient for the system to comply with the harmonic standard for photovoltaic generators without the use of harmonic compensation structures or active harmonic filters. The evaluation of the harmonic distortion behavior of photovoltaic generators as a function of the synchronization strategy used in the inverter controller is the principal work contribution.